The Capacity of Changing the Competition Regime in Romania - Lucia Irinescu (CES Working Papers, 2014)
The policy in the competition field represents the engine of a market. The competition on the internal market improves the competition capacity on the international markets and meets consumers' expectations that shall have the possibility to choose among a larger and cheaper range in terms of price of products and services. The competition freedom is not an absolute one, but it is limited by legal provisions determined by the need to ensure an honest competition.
Keywords: L40; 330; competence; evolution in international plan; policy in the competition field; tools to fight against the anti-competition effects Romania